Fortifikasi Chlorella Pada Roti Manis Sebagai Inovasi Makanan Sehat - Iriani, Dian; Putri Alvin, Okthavia; W Sidauruk, Santhy; Hasan, Bustari; Sari, N Ira (Jurnal Teknologi dan Industri Pertanian Indonesia, 2024)
Bread is a processed food made from wheat flour fermented with yeast and processed by baking. There are various types of bread, one of which is sweet bread. Sweet bread is bread that is consumed more often, has a sweet taste, and is easy to consume anytime and anywhere. This research aims to determine the effect of Chlorella sp powder fortification on the organoleptic and chemical quality characteristics of sweet bread. The research method used was an experimental method with 4 levels of treatment, namely without Chlorella powder (C0), 0,5 % Chlorella powder. (C0,5), 1,0% Chlorella powder. (C1,0), and 1,5% Chlorella powder. (C1,5). The parameters tested in this study were organoleptic and proximate tests (moisture, ash, protein, fat, carbohydrate, and crude fiber). Based on organoleptic testing, the addition 1,0% of chlorella powder in the making of chlorella sweet bread was the best treatment, with the characteristics of a non-mouldy, attractive, and green appearance (6,95), a rather strong bread aroma and a slight aroma typical of Chlorella (7,56), the taste is quite sweet, typical of sweet bread and slight taste of Chlorella (7,99), soft texture (6.79) and the bread development volume was 1.47 cm3. Meanwhile, the proximate values of chlorella sweet bread in 1,0% fortification of chlorella powder were moisture (25,38%), ash (1,15%), protein (5,68%), fat (4,58%), carbohydrates (61,01%), and crude fiber (2,21%).